Managing Multiple Roles: Work-Family Policies and Individuals’ Desires for Segmentation - Rothbard, Nancy P.; Phillips, Katherine W.; Dumas, Tracy L. (Organization Science, 2005)
As workers strive to manage multiple roles such as work and family, research has begun to focus on how people manage the boundary between work and nonwork roles. This paper contributes to emerging work on boundary theory by examining the extent to which individuals desire to integrate or segment their work and nonwork lives. This desire is conceptualized and measured on a continuum ranging from segmentation (i.e., separation) to integration (i.e., blurring) of work and nonwork roles. We examine the fit between individuals’ desires for integration/segmentation and their access to policies that enable boundary management, suggesting that more policies may not always be better in terms of job satisfaction and organizational commitment. Using survey methodology and a sample of 460 employees, we found that desire for greater segmentation does moderate the relationship between the organizational policies one has access to and individuals’ satisfaction and commitment. People who want more segmentation are less satisfied and committed to the organization when they have greater access to integrating policies (e.g., onsite childcare) than when they have less access to such policies. Conversely, people who want greater segmentation are more committed when they have greater access to segmenting policies (e.g., flextime) than when they have less access to such policies. Moreover, the fit between desire for segmentation and organizational policy has an effect on satisfaction and commitment over and above the effects of demographic characteristics such as age, gender, marital status, income, number of children, and the ages of those children.